The Influence Of Virtual Reality Learning Media On The Vocabulary And Pronunciation Mastery Of Class Vii Students In The English Subject Of An-Nisa Gumukmas Middle School Students In 2023 - Hatikah, Bafadal; priawasana, Endra; Darsan, Darsan (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
VR learning media in the learning process of mastering students' vocabulary and pronunciation in the long term will help them communicate better in English. This research uses a quantitative cause and effect (causalistic) research method in looking at the relationship of variables to the object under study. The population in this research in class VII children/students, An-Nisa Gumukmas Middle School, Jember, a total of 33 students. In this research, data analysis techniques used inferential statistics, Android-based Virtual Reality Learning Media on Vocabulary Mastery and Pronunciation in English Subjects for Class VII, An-Nisa Middle School Gumukmas 2023 will have a real impact on improving Vocabulary Mastery and Pronunciation skills in learning English